University Experience during the First Two Waves of COVID-19: Students' Experiences and Psychological Wellbeing - Valentina Lucia La Rosa; Elena Commodari (MDPI AG, 2023)
Background: This study aimed to analyze Italian university students' psychological needs, learning experiences, and wellbeing during the first two waves of the COVID-19 pandemic. Methods: The study was carried out during the first wave of the pandemic, and then during the second. A total of 1230 university students (654 in stage 1 and 576 in stage 2) completed a battery of validated questionnaires exploring students' experiences in distance learning, perceived health risks related to COVID-19, and psychological wellbeing. Results: MANOVA showed a significant main effect of the pandemic stage on students' learning experience and wellbeing. In particular, students were more distracted and concerned about their academic careers during the second phase of the pandemic than in the first. Furthermore, the pandemic stage also significantly affected health risk perceptions and fear of COVID-19, which were higher during the second wave of the pandemic. Female gender and concern for a university career were significant risk factors for high levels of negative affectivity and low levels of positive affectivity during the pandemic. In contrast, adherence to COVID-19 restriction measures and good family support were protective factors. Conclusions: It is essential to promote adequate university psychological services to support university students who have experienced the adverse psychological effects of the pandemic and enhance the resilience factors needed to improve their wellbeing in the post-pandemic period.